2021
DOI: 10.1021/acs.jpclett.1c01623
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Nonequilibrium Dynamics on Second-to-Microsecond Time Scales: Application of Time-Resolved X-ray Diffraction and Dynamic Compression in Ice

Abstract: The study of nonequilibrium transition dynamics on structural transformation from the second to microsecond regime, a time scale between static and shock compression, is an emerging field of high-pressure research. There are ample opportunities to uncover novel physical phenomena within this time regime. Herein, we briefly review the development and application of a dynamic compression technique based on a diamond anvil cell (DAC) and time-resolved X-ray diffraction (TRXRD) for the study of time-, pressure-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
0
2
0
1
Order By: Relevance
“…Although thermodynamics provides the driving force to bring the system from one well to another, effective activation energy (Q eff ) is required to overcome an energy barrier (Q) for completing the transition. In other studies, [53] it is found that the Q eff decreases exponentially with the pressurizing rate. The points mentioned here are schematically illustrated in Fig.…”
Section: Influence Of Pressurizing Rates On Phase Transitionmentioning
confidence: 68%
“…Although thermodynamics provides the driving force to bring the system from one well to another, effective activation energy (Q eff ) is required to overcome an energy barrier (Q) for completing the transition. In other studies, [53] it is found that the Q eff decreases exponentially with the pressurizing rate. The points mentioned here are schematically illustrated in Fig.…”
Section: Influence Of Pressurizing Rates On Phase Transitionmentioning
confidence: 68%
“…But as soon as temperature is above 74 K, particularly above the temperature of the liquid nitrogen, the compression rate starts to rise exponentially. It is natural to apply so called Arrhenius equation 24 29 …”
Section: Synthesis Of - By Fast Compressionmentioning
confidence: 99%
“…Even though it is usually used when P is constant, one can adapt it to describe phase transformation when pressure is changing (see Refs. 27 29 ). In the equation above is an activation energy, C is a constant related to the material, is the Boltzman constant and is a phase growth rate at a given temperature 27 29 .…”
Section: Synthesis Of - By Fast Compressionmentioning
confidence: 99%
“…此外, dDAC与高低温装置结合, 扩展了P-T相图的 研究范围, 提供了毫秒和微秒时间尺度的高压非平 衡过程研究的新能力. 同时, dDAC和时间分辨XRD 结合极大扩展了高压非平衡态的研究手段, 使得诸 多新现象得以发现, 如最近Lin等发现冰、硅的相 变路径和机制表现出高压加载速率依赖性 [18,19] . HPCAT和Petra III的极端条件束线站等, 纷纷 发展了快速检测和快速加载技术 [20,21] .…”
Section: 引 言unclassified